Corner of Beacon and Fairfield Streets, ca. 1880 - Unknown (Tufts Archival Research Center, 2005)
Street level view looking southeast from the corner of Beacon and Fairfield Streets. View is of a single dwelling. Snow is seen in the image. Residence of Charles H. Taylor, 1905-11. 10 1/4 x 10 Photographs